KEEPING THE BODY IMMUNE IN ISLAMIC PERSPECTIVE IN PANDEMIC TIMES - Samsuddin, Samsuddin; Misbahuddin, Misbahuddin; Hamka, Hamka; Ardi, Ardi (Universitas Islam Negeri Alauddin Makassar, 2021)
This research is about maintaining the body's immunity from an islamic perspective during a pandemic. Health is a very attentive thing in Islam, so Islam recommends that you always be able to maintain health so that your body's immune or immune system can stay better and stay strong. This library research aims to understand the urgency of health in Islam and maintain immunity in Islam. This study uses a descriptive method by describing the information in the relevant library materials. The data collection technique in this study is a documentary technique. Namely, information is extracted through documents from various library materials. It is analyzed using content analysis, namely, examining the object of discussion through analysis of books, essays, magazines, articles, and all forms of communication that can be analyzed. The results of this study indicate that the body's immunity or immunity in Islam is adequate rest, eating halal and good food and not excessive (in moderation), and regular exercise. Apart from adequate rest, adequate nutrition, and regular exercise. It is also recommended to maintain mental health, which of course, influences on increasing one's immunity or immunity by constantly reading the Qur'an, praying, and remembering Allah.